THE EFFECT OF UNIVERSITY STUDENTS' TIME MANAGEMENT SKILLS ON CAREER DEVELOPMENT PERFORMANCE (Third Sector Social Economic Review, 2022)
University period is a process where different activities that will shape their future lives for students. Today's living conditions, with the effect of developments in the field of technology, have focused on speed more than ever before and have caused time pressure in every aspect of individuals' lives. Students, on the other hand, give more importance to career development during the university period in order to increase their employment opportunities. In this study, it is aimed to examine the effects of university students' time management skills and sub-dimensions on career development performance. SPSS 22 and AMOS 24 programs were used in the analysis of the data collected from 617 students at two state universities in Ankara with convenience sampling method. Normality analysis, validity and reliability tests, confirmatory factor analysis, descriptive statistics, regression analysis were performed on the data. As a result of the analysis of the collected data, it was determined that the time management skills of university students affect their career development performance. Therefore, it has been clearly understood that university students need to increase their time management skills in order to use time effectively and efficiently.
Keywords: Time Management Skills; Time Planning; Career; Career Development Performance